Prospect Theory and Stock Returns: An Empirical Test - Barberis, Nicholas; Mukherjee, Abhiroop; Wang, Baolian (Review of Financial Studies, 2016)
We test the hypothesis that, when thinking about allocating money to a stock, investors mentally represent the stock by the distribution of its past returns and then evaluate this distribution in the way described by prospect theory. In a simple model of asset prices in which some investors think in this way, a stock whose past return distribution has a high (low) prospect theory value earns a low (high) subsequent return, on average. We find empirical support for this prediction in the cross-section of stock returns in the U.S. market, and also in a majority of forty-six other national stock markets. ( JEL D03) Received November 19, 2014; accepted May 20, 2016, by Editor Stefan Nagel.